The Association Between Obesity Indices and Non-Alcoholic Fatty Liver Disease in Patients with Ankylosing Spondylitis - Kutluk, Oznur; Dabak, Nimet Ezgi; Yucel, Ayca Ayse; Alparslan, Ahmet Sukru; Cay, Fatih (Archives of Rheumatology, 2025)
Background/Aims: This study aimed to investigate the relationship between obesity indices and non-alcoholic fatty liver disease (NAFLD) in patients with ankylosing spondylitis (AS). Materials and Methods: A total of 170 patients with AS were included in this observational study with both prospective and retrospective components. Anthropometric measurements (height, weight, waist circumference [WC]) were prospectively recorded by the investigators during routine clinical visits. Obesity indices, including body mass index (BMI), WC, and waist-to-height ratio (WHtR), were calculated. Non-alcoholic fatty liver disease was diagnosed based on existing abdominal ultrasonography reports. Laboratory data, including liver enzymes, lipid profiles, and inflammatory markers, were retrospectively collected. The diagnostic performance of WC for NAFLD was assessed using receiver operating characteristic (ROC) curve analysis. Results: Non-alcoholic fatty liver disease was detected in 57% of AS patients. Higher BMI and WHtR were significantly associated with both the prevalence and severity of NAFLD (P < .001). Patients with NAFLD exhibited significantly higher levels of C-reactive protein, triglycerides, and alanine aminotransferase, as well as lower high-density lipoprotein levels, compared to those without NAFLD (P < .05). Additionally, the aspartate aminotransferase/alanine aminotransferase ratio was <1 in 66% of NAFLD patients, suggesting its potential as a biochemical marker for NAFLD in AS. The ROC analysis identified WC cutoff values of 100 cm for males and 90 cm for females, demonstrating high sensitivity and specificity in predicting NAFLD. Conclusion: Obesity is strongly associated with NAFLD in AS patients. Body mass index and WHtR may serve as valuable indicators for assessing hepatic steatosis risk. Routine metabolic evaluations, including obesityrelated parameters and liver enzyme levels, could facilitate the early detection of NAFLD in AS patients. Further prospective studies are warranted to clarify the causal relationship between obesity and liver involvement in AS. Cite this article as: Kutluk O, Dabak NE, Yucel AA, Alparslan AS, H, Cay F. The association between obesity indices and non-alcoholic fatty liver disease in patients with ankylosing spondylitis. Arch Rheumatol. 2025;40(4):482-491.